A heterospin pressure sensor1. Issue 30 (14th August 2015) - Maryunina, Kseniya Yu.; Zhang, Xiao; Nishihara, Sadafumi; Inoue, Katsuya; Morozov, Vitaly A.; Romanenko, Galina V.; Ovcharenko, Victor I.
<x xml:space="preserve">Abstract</x> The spin transition temperature of the Cu(ii)-nitroxide complex was found to shift by approximately 100 K toward higher temperatures when the hydrostatic pressure increased to ∼0.04 GPa.